2006
DOI: 10.1021/cm051990w
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Growth of Incommensurate, Polycrystalline, Lying-Down Pentacene Thin Films on Au(111)

Abstract: Pentacene, as well as other polyacenes, is known to adsorb on metal surfaces in a lying-down geometry, that is, with the molecular plane parallel to the surface. Here we show using scanning tunneling microscopy that the lying-down pentacene monolayer seeds the growth of a multilayer polycrystalline film in a layerby-layer fashion, with the molecular planes parallel to the substrate surface. Growth in the submonolayer region is characterized by a large number of ordered molecular structures as coverage increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 26 publications
4
56
1
Order By: Relevance
“…2b). The situation is similar to pentacene adsorption on Au(1 1 1) [11,12] and Au(1 0 0) [25]. Apart from the three predominant directions, there is a broad distribution of relative angles between the molecular chains.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…2b). The situation is similar to pentacene adsorption on Au(1 1 1) [11,12] and Au(1 0 0) [25]. Apart from the three predominant directions, there is a broad distribution of relative angles between the molecular chains.…”
Section: Resultsmentioning
confidence: 77%
“…The chain is 15.6 Å wide with the inter-chain separation of 28 Å . On Au (1 1 1), pentacene form a number of ordered structures in the striped form: Kang and Zhu observed five phases by STM, two of which having unit cells of 15.1 Å · 7.5 Å , 96°and 15.5 Å · 6.4 Å , 82°, respectively [12]. Parkinson et al reported a high density phase with a unit cell of 15 Å · 5.76 Å , 90° [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The persistence of the surface-state in the case of DIP deposition reflects the weakness of the molecule-substrate interaction, as observed with most other organic molecules such as, e.g., PTCDA, CuPc, FePc, HBC, NTCDI, BDG, 6T, DH6T, pentacene, etc. [9,23,31,[34][35][36][37][38][39] A much stronger (and rarer) interaction becomes evident from the data for the F 16 CuPc layers. It is plausible that this interaction arises from a partial charge transfer from Au to F 16 CuPc.…”
Section: Resultsmentioning
confidence: 87%
“…12,13 Thin films of flat-oriented molecules on metals have been seldom reported, i.e., only when the substrate periodicity closely matches that of the pentacene bulk planes. [14][15][16] So far, no lying-down layers of pentacene have been reported on dielectric substrates.…”
Section: ' Introductionmentioning
confidence: 99%